Trypanosoma brucei brucei is more pathogenic in rats compared to mice, making rats a better candidate for the relevant research studies - Karimat Hussain; Shola Ola-Fadunsin; Idris Lawal; Sani Adamu; Saliu Ameen (The Iranian Journal of Veterinary Science and Technology, 2021)
Trypanosomosis is an economically important disease that has raised great and diverse kinds of research using different types of animals. Hence, this study is aimed at determining the better laboratory animal between the Swiss albino mice and Wistar albino rats in Trypanosoma brucei brucei studies. This study assessed the pathogenesis of T. b. brucei in Swiss albino mice and Wistar albino rats by probing the level of parasitemia, mean temperature, mean weight, hematological and histopathological parameters caused by the hemoprotozoan. Twenty laboratory animals, of mice (10) and rats (10) were grouped in two (control (5) and infected (5)), with the infected group inoculated with the blood protozoan intraperitoneally. Trypanosoma b. brucei was detected in the blood of both laboratory animals on day one post-infection, with all the infected animals dying between day seven and eight post-infection. The protozoan exerted a significant (p < 0.05) effect on the mean temperature, mean weight, and hematological parameters of the infected animals. Pathological effects of T. b. brucei infection were seen in the liver and lungs of mice, and the liver, lungs, kidney and spleen of rats. The pathogenesis of T. b. brucei was more severe in rats compared to mice based on the studied parameters. These findings showed that rats are better candidates for T. b. brucei studies.